KEPUASAN KERJA DOSEN UNIVERSITAS NEGERI YOGYAKARTA (UNY) - Sukanti Sukanti (LPPM UNY, 2008)
This research is aimed to describe (1) the active role of hygiene factor in reducing the dissatisfaction of lecturers’ working in YSU, (2) the role of motivators in increasing the satisfaction of working of lectures in YSU, (3) the difference hygiene factor between the female and male lectures, and (4) the difference motivator factor between the female and male lectures. The population of this research is the lectures of Yogyakarta State University (YSU). The sum of them is 903 people; consist of 612 male lectures and 291 female lectures. The sample of this research is 180 lectures of YSU which consists of 92 male lectures and 88 female lectures. The sample is determined by the random sampling techniques. This research uses the questioners as the instrument. Meanwhile, the questioners are adapted from the research of Syptak, Marsland and Ulmer. Prior, the questioners are applied to collect the data; then the research is tested to know the validity and reliability of the instrument. All of the 42 questions of the research are admitted as valid with the correlation point and the lowest total is 0, 36. Meanwhile the highest total is 0, 84 reliabilities with the Cronbach Alpha shows 0,951. The data analysis technique is descriptive with the percentage and t experiment. This research shows that (1) although some of the lectures of YSU state that the institution’s policies are unfair especially in giving the salary, honorarium and bonus, most of them (73, 89%) state that the hygiene is able to reduce the dissatisfaction of their working. Most of the lectures of YSU (73, 89 %) state that the motivator factor is able to increase the satisfaction of their working. There is no any significant difference between the hygiene factor of male lectures and female lectures in reducing the dissatisfaction t counted is 0, 55 and t table is 1, 980. Both of male (72, 83 %) and female lectures (75%), most of them state the existence of hygiene factor in YSU is able to reduce the dissatisfaction of their working. There is no any significant difference between the motivator of male lectures and female lectures in increasing the satisfaction of lectures working. Both of male and females lectures are mostly 73, 91 % and 73, 86 % state that the existence of motivator factor in YSU is able to increase their satisfaction of working